Effects of Cholesterol and Solution pH on Daptomycin-bilayer Interactions - Samuel R. Pennock; Maggie Cortes; Megha D. Salecha; Neil X. Sevilla; Nicole R. Rementer; Kevin Rana; Luke C. Hicks; Emmaleigh Fox; Ahmed Grine; Patience S. Hammel; Timothy D. Vaden; Benjamin R. Carone; et al. (The Journal of Membrane Biology, 2026)

Sediment response to stream restoration in an agricultural watershed - John W. Clune; Gregory B. Noe; Matthew Cashman; Jessica D. DeWitt; Joseph M. Bell; Mitchell R. Weaver; James E. Colgin; Thomas R. Doody; Eliza L. Gross; Victor S. Cortes (Ecological Engineering, 2026)

Natural reproductive modulators in aquaculture: endocrine mechanisms, microalgal and plant-derived bioactives, and sustainability perspectives - Jaynos R. Cortes; John Lloyd F. Penionez; Ciara Mie V. Paragua; Christian C. Respecia; Gino G. Ulit; Zyril A. Mayakie (Frontiers in Marine Science, 2026)
Synthetic hormonal induction is an established tool in modern aquaculture for overcoming reproductive dysfunction, synchronizing spawning, inducing final gamete maturation, and supporting reliable seed production. Growing interest in complementary reproductive strategies has stimulated research on natural bioactive compounds that may support reproduction through endocrine, nutritional, metabolic, and antioxidant pathways. This review critically evaluates microalgal and plant-derived reproductive bioactives in relation to conventional hormonal induction, with particular emphasis on the strength and directness of mechanistic evidence. Microalgal compounds evaluated include long-chain polyunsaturated fatty acids (LC-PUFAs), carotenoids, sterols, and antioxidant polysaccharides, whereas plant-derived compounds include phytoestrogens, flavonoids, saponins, alkaloids, and terpenoids. Available studies associate selected interventions with measurable reproductive endpoints, including gonadal development, fecundity, gamete quality, fertilization, hatchability, spawning performance, and offspring survival. As one study-specific example, pituitary extract treatment in African catfish produced 89.23% fertilization, 93.31% hatchability, 87.16% survival, and 69.41% fry production; however, such values cannot be generalized across interventions because reproductive studies differ substantially in species, compounds, doses, treatment duration, reproductive stage, and outcome definitions. Microalgal LC-PUFAs and carotenoids are supported primarily by evidence of nutritional, membrane-associated, metabolic, and antioxidant reproductive support, whereas direct endocrine effects remain less consistently demonstrated. Plant-derived bioactives show greater mechanistic heterogeneity, with responses frequently dependent on compound identity, dose, species, sex, and reproductive stage. Current evidence therefore supports natural bioactives mainly as complementary tools for broodstock conditioning, gamete support, and reproductive management rather than universal substitutes for conventional hormonal induction. Major limitations include heterogeneous protocols, inadequate dose standardization, species-specific responses, limited direct endocrine validation, insufficient long-term safety assessment, commercialization constraints, and regulatory uncertainty. Future research should prioritize standardized dose-response experiments, direct hormonal and molecular measurements, chemically characterized preparations, long-term and multigenerational safety assessment, and commercially relevant hatchery trials. Overall, natural reproductive bioactives have considerable potential within integrated reproductive-management strategies, but their practical application should be guided by mechanistic evidence, species-specific validation, and clearly defined reproductive objectives.

Correction: A thesaurus for improved communication and data integration in sandy beach ecosystem research - Senem Onen Tarantini; Jessica Titocci; Andrea Tarallo; Omar Defeo; Thomas Schlacher; Guilherme Corte; Carlos Alberto de Moura Barboza; Leonardo Lopes Costa; Ivan Franco Rodil; Linda R. Harris; Jeffrey A. Sibaja-Cordero; Martina Pulieri; et al. (Earth Science Informatics, 2026)

A thesaurus for improved communication and data integration in sandy beach ecosystem research - Senem Onen Tarantini; Jessica Titocci; Andrea Tarallo; Omar Defeo; Thomas Schlacher; Guilherme Corte; Carlos Alberto de Moura Barboza; Leonardo Lopes Costa; Ivan Franco Rodil; Linda R. Harris; Jeffrey A. Sibaja-Cordero; Martina Pulieri; et al. (Earth Science Informatics, 2026)

Immersion-based application of Origanum vulgare extract improves growth and pigmentation in Kappaphycus alvarezii under field conditions - Angela Jan Cajate; Aljohn E. Calunod; Jay D. Tering; Kevin Rey A. Guiritan; Kris Angeli Sanchez-DelosReyes; Jaynos R. Cortes (Frontiers in Marine Science, 2026)
Environmental stress-associated tissue deterioration remains an important challenge in the cultivation of Kappaphycus alvarezii . This study evaluated the effects of immersion-based application of Origanum vulgare extract on the growth performance and pigmentation of K. alvarezii cultivated under field conditions. In vitro antibacterial assays showed inhibitory activity of the extract against Staphylococcus aureus (21 mm inhibition zone) and Escherichia coli (19 mm inhibition zone). An in vivo experiment was conducted using four immersion treatments: control, 5 min, 15 min, and 25 min exposure durations. Growth performance differed significantly among treatments, with the 15-min immersion treatment producing the highest final weight (259.67 ± 13.05 g). Pigmentation scores were also significantly higher in the 15- and 25-min treatments compared with the control. Regression analysis suggested that intermediate immersion durations between approximately 15 and 18 min may provide favorable growth responses, although this estimate should be considered preliminary because only four treatment durations were evaluated. Overall, immersion-based application of O. vulgare extract improved growth performance and maintained better thallus pigmentation under field conditions. These findings support the potential use of plant-derived bioactive treatments as functional approaches for improving thallus condition in K. alvarezii aquaculture systems. However, the present study did not directly quantify disease incidence, pathogen abundance, or tissue mortality; therefore, interpretations regarding ice-ice disease mitigation should be considered preliminary.

Species-specific antifungal resistance trends in yeast bloodstream isolates causing candidemia before, during, and after the COVID-19 pandemic: insights from the INVIFAR Mexican multicenter network - Rogelio J. de Treviño-Rangel; Hiram Villanueva-Lozano; María F. González-Lara; Paula A. Castaño-Jimenez; Reyna E. Corte-Rojas; María A. Quevedo-Ramos; Laura K. Avilés-Benítez; Eduardo López-Gutiérrez; José M. Feliciano-Guzmán; Martha Dorado-del Río; Zaira L. Clemente-Callejas; Aarón Molina-Jaimes; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Lithium clay mineralization in the McDermitt volcano-sedimentary deposit, Oregon, USA - F. Putzolu; R. N. Armstrong; L. E. Hepburn; N. Bompard; A. Boyce; E. A. Cortes-Calderon; E. R. Tonks; R. Ball; R. J. Herrington (Mineralium Deposita, 2026)
The McDermitt caldera (Oregon–Nevada, USA) hosts the largest volcano-sedimentary (VS) Li resource globally. This study presents an integrated geological, mineralogical, and isotopic investigation of the McDermitt deposit in Oregon, with the aim of constraining the processes responsible for Li enrichment in clay-type VS Li mineralization. Our study reveals that Li mineralization occurs in stratiform lacustrine units composed of hectorite-bearing claystones interbedded with siliceous–carbonate beds and altered ash fall units. Lithium enrichment is mainly controlled by the formation of Mg–Li smectites (hectorite) associated with hydrous silica, and locally by zeolitization of tuffaceous precursors – a pathway that can be explained by devitrification of volcanic glass under near-neutral to slightly alkaline conditions. Geochemical and isotopic data indicate that mineralization formed through fluids at average temperatures of 133 °C and δD values of − 107‰, consistent with heated meteoric waters in a geothermal setting. Unlike the nearby Thacker Pass deposit, illitization of smectite did not occur, reflecting differences in the total amount of Li available and in the pH chemistry of deeper fluids circulating on a caldera-scale.

Considerations on the process of target selection for the Comet Interceptor mission - C. Snodgrass; E. Mazzotta Epifani; C. Tubiana; J.P. Sánchez; N. Biver; L. Inno; M.M. Knight; P. Lacerda; J. De Keyser; A. Donaldson; N.J.T. Edberg; M. Galand; et al. (Icarus, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

In-situ response to injury shows the short-term impacts of elevated temperatures on two mediterranean corals, Cladocora caespitosa (Linnaeus, 1767) and Balanophyllia Europaea (Risso, 1827) - L. Bisanti; M. Cammarata; C. La Corte; F. Bertini; M. Staropoli; L. T. Marcianò; L. Scirè Calabrisotto; D. Parrinello; M. G. Parisi; V. Catania; R. Chemello; M. Dara (Marine Biology, 2026)
Among the main drivers of critical changes in marine environments is global warming, largely caused by anthropogenic activities. Growing evidence suggests that climate change is rapidly and detrimentally impacting ecosystems worldwide, challenging the survival of marine organisms, including corals. We carried out in-situ experiments to assess the effect of seasonal temperature changes on short-term injury responses of immune-related enzymes (phenoloxidase, glutathione peroxidase and lysozyme) and host-associated bacterial communities in two Mediterranean endemic species: the colonial coral Cladocora caespitosa and the solitary coral Balanophyllia europaea . Our results show that both corals demonstrated strong enzymatic responses in immune parameters to injury under winter conditions. However, during the summer period, there was an alteration (significant in at least one parameter) of enzymatic activities, outlining a general pattern of enhanced effects of elevated temperatures on constitutive activities but a suppressive impact on injury responses. While winter corals showed relative stable bacterial communities, under summer conditions, several taxa of coral-associated microbiota generally associated with coral diseases shifted in abundance and composition. These changes suggest that environmental cues of increasing temperatures could affect coral health and survival, potentially hindering their ability to respond following physical disturbances under summer seawater conditions.

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Effects of ambient temperature on under-five mortality: a nationwide space-time-stratified case-crossover study in Brazil - Ismael H. Silveira; Poliana Rebouças; Julia Pescarini; Taísa R. Cortes; Beatriz F.A. Oliveira; Danielson J.D. Neves; Aline dos Santos Rocha; Rita de Cássia Ribeiro-Silva; Mauricio L. Barreto; Otavio T. Ranzani; Enny S. Paixao (Environmental Research, 2025)

Performative planning? Evaluating coexistence and procedural justice in Queensland's gas–agriculture interface - Shay D. Dougall; Josephine Gillespie; Adem Sav; Javier Cortes Ramirez; Melissa R. Haswell (Journal of Rural Studies, 2025)

In utero exposure to estrogenic bisphenol analogues increases mammary tissue stiffness - Jillian M. Poska; Clarissa Wormsbaecher; Brittney M. Cumbia; Madeline R. Price; Marcos Cortes-Medina; Jacob Holter; Shashwat Agarwal; Xiaokui Molly Mo; Jonathan W. Song; Craig J. Burd (Reproductive Toxicology, 2025)

Sandy beaches within meta-social-ecological systems: An integrated framework for ecology, management, and conservation - Omar Defeo; Guilherme Corte; Carlos A.M. Barboza; Paula Debiasi; Leonardo Lopes Costa; Michael Elliott; Lucia Fanini; Linda R. Harris; Nelson Rangel-Buitrago; John Baxter; Alberto Basset; Anton McLachlan (Estuarine, Coastal and Shelf Science, 2025)

From dark horse to front-runner: vascular contributions to brain health - Aditi Gupta; Paulo W. Pires; Sandra A. Billinger; S. Thomas Carmichael; Constanza J. Cortes; Richard Daneman; Xiao Hu; Daniela Kaufer; Swati R. Levendovszky; Farzaneh A. Sorond; Chelsea M. Stillman; Stefano Tarantini; et al. (GeroScience, 2025)

Corrigendum to “Linking monitoring data and timescales of mafic recharge during the 2013–17 eruption at Volcán de Colima, Mexico” [Journal Volcanology and Geothermal Research 460 (2025) 108285] - Gerallt E. Hughes; Chiara Maria Petrone; Hilary Downes; Nick R. Varley; Dulce Vargas-Bracamontes; Raul Arámbula-Mendoza; Edgar A. Cortes-Calderon; Yannick Buret (Journal of Volcanology and Geothermal Research, 2025)

Linking monitoring data and timescales of mafic recharge during the 2013–17 eruption at Volcán de Colima, Mexico - Gerallt E. Hughes; Chiara Maria Petrone; Hilary Downes; Nick R. Varley; Dulce Vargas-Bracamontes; Raul Arámbula-Mendoza; Edgar A. Cortes-Calderon; Yannick Buret (Journal of Volcanology and Geothermal Research, 2025)

Extreme Climatic Events and Urbanization Impacts on Sandy Beach Ecosystems: A Field Experiment before and after Hurricane Lee - Miranda Goad; Tara Thompson; Zachary Briggs; Allie Durdall; Kristin R. Wilson Grimes; Guilherme Corte (Estuaries and Coasts, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

Optimal choice of closest approach distance for a comet flyby: Application to the Comet Interceptor mission - J. De Keyser; N.J.T. Edberg; P. Henri; H. Rothkaehl; V. Della Corte; M. Rubin; R. Funase; S. Kasahara; C. Snodgrass (Planetary and Space Science, 2025)

Prenatal exposure to ambient air pollution and subsequent risk of lower respiratory tract infections in childhood and adolescence: A systematic review - Maxine Pepper; Poliana Rebouças; Ila R. Falcão; Nuria Sanchez Clemente; Rachel Lowe; Rochelle Schneider; Julia M. Pescarini; Gervásio F. dos Santos; Roberto FS. Andrade; Taísa R. Cortes; Otavio T. Ranzani; Elizabeth B. Brickley; et al. (International Journal of Hygiene and Environmental Health, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

In situ plasma and neutral gas observation time windows during a comet flyby: Application to the Comet Interceptor mission - J. De Keyser; N.J.T. Edberg; P. Henri; H.-U. Auster; M. Galand; M. Rubin; H. Nilsson; J. Soucek; N. André; V. Della Corte; H. Rothkaehl; R. Funase; et al. (Planetary and Space Science, 2024)

How does warmer sea water change the sensitivity of a Mediterranean thermophilic coral after immune-stimulation? - L. Bisanti; C. La Corte; M. Dara; F. Bertini; D. Parrinello; R. Chemello; M. Cammarata; M. G. Parisi (Coral Reefs, 2024)
Anthropogenic climate change is warming sea water worldwide, pushing the limits of tolerance for marine organisms and driving a decline in biodiversity. The risk of thermal anomalies has increased particularly in the Mediterranean region over the last 30 yrs, where intense warming has been identified as one of the main stressors in coastal regions. To determine the influence of warmer conditions on the immunity of an endemic Mediterranean coral species, different immune activity parameters were compared in response to elevated temperature (~ 28 °C) and the presence of a pathogen-associated molecular pattern— Escherichia coli lipopolysaccharide (LPS)—as an elicitor of the innate immune response of Astroides calycularis . Immune parameters, which included phenoloxidase-like, glutathione peroxidase, lysozyme-like, alkaline phosphatase, and esterase enzyme activity, were measured over time after LPS balneation (0-, 12-, 48-, and 120 h time point). All five enzymes demonstrated constant values under environmental conditions (~ 23 °C), indicating a constituent activity. LPS at environmental temperature induced significant upregulation immediately after exposure (0 h-time point), demonstrating an immune response to the pathogen elicitor. Under warmer conditions (~ 28 °C), constituent values increased over time, indicating a shift in the immune strategy to maintain homeostasis. However, warmer sea water, within the summer range experienced by this coral species, impaired the immune response to LPS, delaying it over time. These changes in immune strategy indicate that temperature affects coral immunity and, in thermophilic A. calycularis , results in an energy trade-off that could maintain its health-state through suboptimal conditions during multiple perturbations, such as summertime diseases.

Detection of symptoms induced by vascular plant pathogens in tree crops using high-resolution satellite data: Modelling and assessment with airborne hyperspectral imagery - T. Poblete; J.A. Navas-Cortes; A. Hornero; C. Camino; R. Calderon; R. Hernandez-Clemente; B.B. Landa; P.J. Zarco-Tejada (Remote Sensing of Environment, 2023)

Synthesis and Characterization of a Coagulating Agent from Plantain Peel Starch (Musa paradisiaca), as Coadjuvant in Water Treatment - Camilo Cortes-Pérez; Leymer Pérez-Montalvo; Jorgelina Pasqualino; Jorge R. Puello-Silva; Henry A. Lambis-Miranda (Water, Air, & Soil Pollution, 2023)

Protective role of Portuguese natural mineral waters on skin aging: in vitro evaluation of anti-senescence and anti-oxidant properties - CV Vaz; AS Oliveira; A Silva; L Cortes; S Correia; R Ferreira; L Breitenfeld; J Martinez-de-Oliveira; R Palmeira-de-Oliveira; CF Pereira; MT Cruz; A Palmeira-de-Oliveira (International Journal of Biometeorology, 2022)

Genetic diversity of Chlamydia pecorum detected in sheep flocks from Mexico - M. M. Limón-González; R. Hernández-Castro; F. Martínez-Hernández; J. Xicohtencatl-Cortes; H. Ramírez-Alvarez; E. G. Palomares-Resendiz; E. Díaz-Aparicio (Brazilian Journal of Microbiology, 2022)

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Storylines for practice: a visual storytelling approach to strengthen the science-practice interface - Vivian Juliette Cortes Arevalo; Laura N. H. Verbrugge; Anneke Sools; Marcela Brugnach; Rik Wolterink; R. Pepijn van Denderen; Jasper H. J. Candel; Suzanne J. M. H. Hulscher (Sustainability Science, 2020)
A growing number of scientific publications is available to promote sustainable river management. However, these publications target researchers rather than water management professionals who are responsible for the implementation of management practices. To bridge this science-to-practice gap, we conceptualize and propose a series of steps to prepare effective storylines targeted at a practitioner audience. We developed this approach within a research program that supports integrated and collaborative river management. We prepared three storylines, each based on one scientific publication. The storylines combined text and interactive visuals using the ESRI StoryMaps tool to make them available online. Via focus groups with 44 participants from research and practice, we evaluated the perceived usefulness of and engagement with the content and design. We collected feedback from participants using a survey as well as via audio and screen recordings. Our findings show that we should narrow down the audience of the storylines by tailoring them to the needs of project managers rather than specialized advisors. Therefore, the content should offer more than a visual summary of the research by showing examples of the management application. A more engaging sequence with a clear protagonist is further required to better relate to the problem and the potential application. Although visuals and interactive elements were considered attractive, a multi-disciplinary editorial team is necessary to better complement the visuals’ design to the text. The level of detail of participants’ feedback shows that involving project managers to co-create storylines can be an important step for improvement.

Serum matrix metalloproteinase-9 in children exposed to arsenic from playground dust at elementary schools in Hermosillo, Sonora, Mexico - Leticia García-Rico; Diana Meza-Figueroa; Paloma I. Beamer; Jefferey L. Burgess; Mary K. O’Rourke; Clark R. Lantz; Melissa Furlong; Marco Martinez-Cinco; Iram Mondaca-Fernandez; Jose J. Balderas-Cortes; Maria M. Meza-Montenegro (Environmental Geochemistry and Health, 2020)

Drought impacts to trout and salamanders in cool, forested headwater ecosystems in the western Cascade Mountains, OR - Matthew J. Kaylor; Brian J. VerWey; Alvaro Cortes; Dana R. Warren (Hydrobiologia, 2019)

A morphological database for Colombian anuran species from conservation‐priority ecosystems - Angela M. Mendoza‐Henao; Ángela M. Cortes‐Gomez; Mailyn A. Gonzalez; Oscar Dario Hernandez‐Córdoba; Andres R. Acosta‐Galvis; Fernando Castro‐Herrera; Juan M. Daza; Julio Mario Hoyos; Martha Patricia Ramirez‐Pinilla; Nicolás Urbina‐Cardona; Beatriz Salgado‐Negret (Ecology, 2019)
Species traits provide a strong link between an organism's fitness and processes at community and ecosystem levels. However, such data remain scarce for amphibians in the Neotropics. Colombia is the country with the highest number of threatened amphibians and the second greatest number of amphibian species worldwide. We present a data set containing eight morphological traits for 4,623 museum specimens of the seven largest collections in the country corresponding to 293 species of 14 families. The number of measured specimens per species ranged from 1 to 118 individuals with a median of 8 individuals per species. Overall, this database gathered morphological information for 37.6% of Colombian anuran diversity. Species measured were mainly distributed in the high Andean forest, the páramo, and wetland ecosystems, and was part of a national initiative led by the Instituto Alexander von Humboldt. The morphological traits were selected on the basis of their role in species’ responses to environmental variability and their contributions to ecosystem processes. These traits were related to habitat use, (forearm length, tibia length, femur length, foot length, and foot webbing), predation and food chains (head width and mouth width), and nutrient recycling (snout–vent length). We expect this data set will be used in studies on functional diversity in amphibians and the development of conservation planning for these taxa. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Repellency and Larvicidal Activity of Essential oils from Xylopia laevigata, Xylopia frutescens, Lippia pedunculosa, and Their Individual Compounds against Aedes aegypti Linnaeus - A M D Nascimento; T D S Maia; T E S Soares; L R A Menezes; R Scher; E V Costa; S C H Cavalcanti; R La Corte (Neotropical Entomology, 2017)

The Influence of Fatty Acid Methyl Esters (FAMEs) in the Biochemistry and the Na+/K+-ATPase Activity of Culex quinquefasciatus Larvae - Lilian N. D. Silva; José A. Ribeiro-Neto; Jéssica M. M. Valadares; Mariana M. Costa; Luciana A. R. S. Lima; Luciano A. M. Grillo; Vanessa F. Cortes; Herica L. Santos; Stênio N. Alves; Leandro A. Barbosa (The Journal of Membrane Biology, 2016)

Displacement-based design of steel moment resisting frames with partially-restrained beam-to-column joints - R. Roldán; T. J. Sullivan; G. Della Corte (Bulletin of Earthquake Engineering, 2016)

Is the tiger shark Galeocerdo cuvier a coastal species? Expanding its distribution range in the Atlantic Ocean using at‐sea observer data - A. Domingo; R. Coelho; E. Cortes; B. Garcia‐Cortes; F. Mas; J. Mejuto; P. Miller; A. Ramos‐Cartelle; M. N. Santos; K. Yokawa (Journal of Fish Biology, 2016)
The occurrence of tiger shark Galeocerdo cuvier in the Atlantic Ocean was assessed using at‐sea observer data from multiple pelagic longline fisheries. Geographic positions of 2764 G. cuvier recorded between 1992 and 2013 and covering a wide area of the Atlantic Ocean were compared with the currently accepted distribution ranges of the species. Most records fell outside those ranges in both the Southern and Northern Hemispheres, which strongly suggests that the distribution range of G. cuvier in the open ocean is considerably larger than previously described

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Multiple domestications of the Mesoamerican gene pool of lima bean (Phaseolus lunatus L.): evidence from chloroplast DNA sequences - R. H. Andueza-Noh; M. L. Serrano-Serrano; M. I. Chacón Sánchez; I. Sanchéz del Pino; L. Camacho-Pérez; J. Coello-Coello; J. Mijangos Cortes; D. G. Debouck; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2013)

Tocopherol composition and antioxidant activity of Spanish wild vegetables - Patricia Morales; Ana Maria Carvalho; Mª Cortes Sánchez-Mata; Montaña Cámara; María Molina; Isabel C. F. R. Ferreira (Genetic Resources and Crop Evolution, 2012)

Comparison of genomic DNA extraction techniques from whole blood samples: a time, cost and quality evaluation study - Diego Chacon-Cortes; Larisa M. Haupt; Rod A. Lea; Lyn R. Griffiths (Molecular Biology Reports, 2012)

Intergroup variation in stable isotope ratios reflects anthropogenic impact on the Barbary macaques (Macaca sylvanus) of Gibraltar - Mark R. Schurr; Agustín Fuentes; Ellen Luecke; John Cortes; Eric Shaw (Primates, 2012)

Assessment of instream structures for habitat improvement for two critically endangered fish species - I. Boavida; J. M. Santos; R. V. Cortes; A. N. Pinheiro; M. T. Ferreira (Aquatic Ecology, 2011)

Neural Mechanisms Underlying Learning Following Semantic Mediation Treatment in a Case of Phonologic Alexia - Jacquie Kurland; Carlos R. Cortes; Marko Wilke; Anne J. Sperling; Susan N. Lott; Malle A. Tagamets; John VanMeter; Rhonda B. Friedman (Brain Imaging and Behavior, 2008)

Ecological traits of fish assemblages from Mediterranean Europe and their responses to human disturbance - T. FERREIRA; J. OLIVEIRA; N. CAIOLA; A. DE SOSTOA; F. CASALS; R. CORTES; A. ECONOMOU; S. ZOGARIS; D. GARCIA‐JALON; M. ILHÉU; F. MARTINEZ‐CAPEL; D. PONT; et al. (Fisheries Management and Ecology, 2007)
Mediterranean river systems are characterised by more diverse fish assemblages and regional ecological processes compared with the rest of Europe. A data set from Mediterranean France, Iberia and Greece (∼2000 sites) was used to describe the characteristics of fish assemblages, explore their responses to anthropogenic disturbance and analyse the implications for river quality assessment. There was a southwards decline in species richness per site, but endemicity and proportion of alien species increased. Sites in the eastern Mediterranean had higher endemicity, lower site richness and lower number of alien species than sites in western Mediterranean Europe. Assemblage composition differed between Mediterranean sub‐regions, but was dominated by three major fish types: a salmonid fish type common throughout the study area and two cyprinid‐dominated fish types (in some sub‐regions, Salmo trutta L. is present but not numerically dominant), corresponding to a gradient in hydrological and temperature regimes. Metric responses to perturbation were compared with those found at the European (larger scale) and basin (smaller scale) levels. Overall metric response was weaker in this Mediterranean application. The best responses to human pressure were usually obtained with abundance‐based metrics and included the contribution of naturalised alien species. Some widespread alien species contributed to the response to anthropogenic alteration (notably Cyprinus carpio L. and Lepomis gibbosus (L.)).

Modelling the impact of climate extremes: an overview of the MICE project - C. E. Hanson; J. P. Palutikof; M. T. J. Livermore; L. Barring; M. Bindi; J. Corte-Real; R. Durao; C. Giannakopoulos; P. Good; T. Holt; Z. Kundzewicz; G. C. Leckebusch; et al. (Climatic Change, 2007)

Combining Logistic Models with Multivariate Methods for the Rapid Biological Assessment of Rivers Using Macroinvertebrates - S. V. Oliveira; R. M. V. Cortes (Environmental Monitoring and Assessment, 2006)

ARE GRAY WHALES HITTING “K” HARD? - Sue E. Moore; Jorge Urbán R.; Wayne L. Perryman; Frances Gulland; Hector Perez‐Cortes M.; Paul R. Wade; Lorenzo Rojas‐Bracho; Teri Rowles (Marine Mammal Science, 2001)

Three new monosomic chromosome 5B genetic stocks of bread wheat - A. Mujeeb-Kazi; A. Cortes; V. Rosas; R. Delgado; F. A. Shafiq; A. A. Vahidy (Cereal Research Communications, 2001)

Diamond growth during ultrahigh‐pressure metamorphism of the Kokchetav Massif, northern Kazakhstan - K. De Corte; A. Korsakov; W. R. Taylor; P. Cartigny; M. Ader; P. De Paepe (Island Arc, 2000)
Characteristic features of in situ diamonds can be used to retrace diamond formation during ultrahigh pressure (UHP) metamorphism of the Kokchetav Massif, Kazakhstan. These features include the nitrogen aggregation state in diamond, dissolution features observed on diamond surfaces, and the carbon and nitrogen isotopic composition of the diamonds. The minerals in which the diamonds are included provide additional information and support the view that at least some of the Kokchetav microdiamonds are the products of prograde or peak UHP metamorphism. The coexistence of diamond and graphite is evaluated within this framework.

Detection of Leishmania in Immunocompromised Patients Using Peripheral Blood Spots on Filter Paper and the Polymerase Chain Reaction - L. Campino; S. Cortes; R. Pires; L. Oskam; P. Abranches (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Some Triticum turgidum L. cultivars possessing the chromosome T1BL.1RS substitution - A. Mujeeb-Kazi; A. Cortes; V. Rosas; M. D. H. M. William; R. Delgado (Cereal Research Communications, 1999)